2007
DOI: 10.2134/agronj2006.0136
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Nitrogen Rate and Form on Quality of Putting Greens Cohabited by Creeping Bentgrass and Annual Bluegrass

Abstract: Of the essential nutrients, N fertility generally influences golf course putting green (PG) quality and growth rate most significantly. Despite considerable field research on N fertility of PGs, results interpretation and transfer to practice is complicated by various influential factors; including unrepresentative mowing heights and/or frequency, varying irrigation water quality, undeclared composition of mixed swards, withdrawn cultivars, and/or use of temperature-dependent organic fertilizer sources. A 2-yr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 32 publications
(42 reference statements)
2
21
0
Order By: Relevance
“…Potter et al (1985) found routine applications of ammonium nitrate fertilizer over 7 yr signifi cantly reduced the pH of a silt loam. Schlossberg and Schmidt (2007) found that N treatments containing >50% ammoniacal N significantly increased growth, color, N uptake, and leaf nutrient levels compared to equal treatments containing >50% nitrate N sources. The silt loam root zone would have been less likely to show a pH change than the sand root zone due to inherent buff ering capacity.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Potter et al (1985) found routine applications of ammonium nitrate fertilizer over 7 yr signifi cantly reduced the pH of a silt loam. Schlossberg and Schmidt (2007) found that N treatments containing >50% ammoniacal N significantly increased growth, color, N uptake, and leaf nutrient levels compared to equal treatments containing >50% nitrate N sources. The silt loam root zone would have been less likely to show a pH change than the sand root zone due to inherent buff ering capacity.…”
Section: Discussionmentioning
confidence: 89%
“…Given the relatively short time period (2.5 yr) of the study, it is possible that long-term use of calcium nitrate could have more consistent, negative results on VBG turf than we noticed. Schlossberg and Schmidt (2007) found that N treatments containing >50% ammoniacal N significantly increased growth, color, N uptake, and leaf nutrient levels compared to equal treatments containing >50% nitrate N sources. Their demonstration of ammoniacal N sources yielding better turf conditions than nitrate N sources agrees with our fi ndings that ammonium sulfate and ammonium nitrate occasionally produced better turf than calcium nitrate.…”
Section: Discussionmentioning
confidence: 89%
“…Although putting greens occupy only a small area of a golf course, they consume a disproportionate amount of resources, especially fertilizers (Schlossberg and Schmidt, 2007). Intensive N fertilization is essential for supporting and maintaining putting green quality including color, vigor, root-to-shoot ratio, and disease resistance (Turgeon, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Clipping yield and tissue K increased with N rate (49-441 kg N ha −1 yr −1 ), whereas soil K and soil pH decreased with N rate (Table 3). The increase in tissue K with N observed in turf and forage grasses is largely due to the increased shoot growth demand with increasing N (Hojjati et al, 1977;George et al, 1979;Snyder and Cisar, 2000;Fitzpatrick and Guillard, 2004;Petrovic et al, 2005;Schlossberg and Schmidt, 2007) with a corresponding decrease in soil K (George et al, 1979;Fitzpatrick and Guillard, 2004). The decrease in soil K may also be due to increased leaching loss with increased N rate.…”
Section: Resultsmentioning
confidence: 98%
“…Specifically, approximately 97, 68, 99, and 90% of the N effect was linear for CY, tissue K, soil K, and soil pH, respectively (Table 2). The increase in tissue K with N observed in turf and forage grasses is largely due to the increased shoot growth demand with increasing N (Hojjati et al, 1977;George et al, 1979;Snyder and Cisar, 2000;Fitzpatrick and Guillard, 2004;Petrovic et al, 2005;Schlossberg and Schmidt, 2007) with a corresponding decrease in soil K (George et al, 1979;Fitzpatrick and Guillard, 2004). The increase in tissue K with N observed in turf and forage grasses is largely due to the increased shoot growth demand with increasing N (Hojjati et al, 1977;George et al, 1979;Snyder and Cisar, 2000;Fitzpatrick and Guillard, 2004;Petrovic et al, 2005;Schlossberg and Schmidt, 2007) with a corresponding decrease in soil K (George et al, 1979;Fitzpatrick and Guillard, 2004).…”
Section: Overall Effects Of Nitrogen-potassium Fertilizer and Yearmentioning
confidence: 99%